2016
DOI: 10.1210/en.2016-1349
|View full text |Cite
|
Sign up to set email alerts
|

17β-HSD type 12-like is responsible for maturation-inducing hormone synthesis during oocyte maturation in masu salmon12

Abstract: Abbreviated title: 17β-HSD12-like responsible for DHP production Key terms: 17α,20β-dihydroxy-4-pregnen-3-one, 20β-hydroxysteroid dehydrogenase, 17β-hydroxysteroid dehydrogenase, Oocyte maturation, Granulosa, Masu salmon, Oncorhynchus masou AbstractThe maturation-inducing hormone 17α,20β-dihydroxy-4-pregnen-3-one (DHP) was first identified in the amago salmon. However, although carbonyl reductase-like 20β-hydroxysteroid dehydrogenase (CR/20β-HSD) was reported to convert 17α-hydroxyprogesterone (17OHP) to DHP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…CR/20bhsd mRNA expression levels in follicles showed no response to SPE or HCG at all follicle stages. This result was similar to those of a previous study in which two forms of CR/20β-HSD were identified in masu salmon and the mRNA levels of both CR/20β-HSD typeA and typeB in the forskolin-induced granulosa were not greater than the levels observed in the control group (Ijiri et al, 2017). However, another study of Nile tilapia reported that full-grown (post-vitellogenic) immature follicles incubated with HCG, with centrally located germinal vesicles, induced the short-term expression of CR/20bhsd mRNA within 1-2 h, suggesting that an increase in CR/20bhsd mRNA expression prior to oocyte maturation is responsible for 20β-HSD activity (Senthilkumaran et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…CR/20bhsd mRNA expression levels in follicles showed no response to SPE or HCG at all follicle stages. This result was similar to those of a previous study in which two forms of CR/20β-HSD were identified in masu salmon and the mRNA levels of both CR/20β-HSD typeA and typeB in the forskolin-induced granulosa were not greater than the levels observed in the control group (Ijiri et al, 2017). However, another study of Nile tilapia reported that full-grown (post-vitellogenic) immature follicles incubated with HCG, with centrally located germinal vesicles, induced the short-term expression of CR/20bhsd mRNA within 1-2 h, suggesting that an increase in CR/20bhsd mRNA expression prior to oocyte maturation is responsible for 20β-HSD activity (Senthilkumaran et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In masu salmon, the expression of hsd17β12l mRNA was limited in testis and follicle layers at final maturation (Ijiri et al, 2017). In tilapia, hsd17b12 mRNA showed the same expression pattern.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is well known that SDRs play important roles in steroids and retinoids metabolism [25]. Expression, substrate specificity, and functions of hsd17b, hsd3b, and hsd11b in sex steroids biosynthesis were extensively investigated in several teleosts [41][42][43][44]. In this study, hsd3b7, rdh10b-2, rdh12b, dhrs3, dhrs7b, dhrs9, sdr39u1, hpgd-b1, far1, spra, and decr2 were identified as ovary-enriched genes, while hsd3b1, hsd11b1-b2, hsd11b2, rdh14b, kdsr, and ak7-a were identified as testis-enriched genes.…”
Section: Spatial and Temporal Expression Of Sdrs In Nile Tilapiamentioning
confidence: 99%